Non-Mutated Nucleophosmin 1 Is Recognized by the CD8+ T Lymphocytes of an AML Patient after the Transplantation of Hematopoietic Stem Cells from an HLA-Haploidentical Donor - Nemeckova, Sarka; Alexova-Zurkova, Kamila; Hainz, Petr; Krystofova, Jitka; Mackova, Jana; Roubalova, Katerina; Stastna-Markova, Marketa; Vrana, Milena; Vydra, Jan (Current oncology (Toronto, Ont.), 2022)
Nucleophosmin (NPM1, B23) is a multifunctional phosphoprotein expressed in all tissues. The protein is mainly localized in nucleoli. In hematological malignancies, NPM1 belongs to commonly altered genes. Its mutation, always heterozygous, leads to the re-localization of the NPM1 protein from the nucleolus to the cytoplasm (NPM1c+). NPM1c+ is found in 30% of acute myeloid leukemia (AML). Our study showed that an AML patient, whose leukemia cells carried the NPM1c+ mutation and who was the recipient of allogeneic HSCT from a haploidentical donor, raised a robust allorestricted CD8+ T cell response directed against the NPM1wt protein. Favourably, the response against NPM1wt was not accompanied by side effects such as GvHD. Moreover, the induction of a high NPM1wt-specific response coincided with the decrease in NPM1c+ transcripts detected, implying a beneficial graft versus leukemia effect. On the basis of these results, we suppose that TCRs from allorestricted NPM1wt-specific T cells are worth studying in other recipients of grafts from haploidentical donors as a possible tool for TCR gene therapy.
Keywords: hematopoetické kmenové buňky; mutation; Nucleophosmin; Hematopoietic Stem Cells; akutní myeloidní leukemie; lidé; CD8-pozitivní T-lymfocyty; jaderné proteiny; acute myeloid leukemia; nukleofosmin; CD8-Positive T-Lymphocytes; Nuclear Proteins; Humans; nucleophosmin 1; Leukemia, Myeloid, Acute; T cell response; hematopoietic stem cell transplantation